The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/jo4002036
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Bull’s Horn-Shaped Oligothienoacene with Seven Fused Thiophene Rings

Abstract: A novel bull's horn-shaped oligothienoacene with seven fused thiophene rings (1) based on dithieno[2,3-b:2',3'-d]thiophene (2) was efficiently synthesized. X-ray diffraction data indicate that 1 possesses an extraordinary compressed sandwich-herringbone arrangement and shows strong intermolecular S···C and S···S interactions. In addition, the UV/vis properties, theoretical calculations, and cyclic voltammetry behaviors of 1 are also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The reaction was quenched with saturated solution of ammonium chloride (30 mL) and extracted with CHCl 3 (100 mL) three times. Then, the combined organic phase was washed with brine, and dried over MgSO 4 . Evaporation of the solvent under vacuum resulted in a solid residue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was quenched with saturated solution of ammonium chloride (30 mL) and extracted with CHCl 3 (100 mL) three times. Then, the combined organic phase was washed with brine, and dried over MgSO 4 . Evaporation of the solvent under vacuum resulted in a solid residue.…”
Section: Resultsmentioning
confidence: 99%
“…Considerable attention has been paid to the development of oligothiophenes for use in organic solar cells, 1-2 π-conjugated conducting polymers, [3][4][5][6] high-performance organic field-effect transistors (OFET), [7][8] and organic lightemitting materials. [9][10] Generally, one of the strategies for fine-tuning the HOMO-LUMO gap involves the utilization of extended thiophene subunits 11 and particularly those rigid structures possessing an extended π-conjugation in the ground state, 12 such as thienothiophenes (TTs) and dithienothiophenes (DTTs).…”
Section: Introductionmentioning
confidence: 99%
“…The dithieno[3,2‐b;2′,3′‐d]thiophene (DTT) molecular moiety is one of the most promising substructures for thiophene‐based organic semiconductors due to outstanding optoelectronic performances, resulting from remarkable intrinsic molecular properties and possible strong intermolecular interactions . So far, all reported DTT‐containing organic semiconductors exhibit high charge carrier mobility and good environmental stability.…”
Section: Introductionmentioning
confidence: 99%
“…The dithieno[3,2-b;2',3'-d]thiophene (DTT) molecular moiety is one of the most promising substructures for thiophene-based organic semiconductors due to outstanding optoelectronic performances, resulting from remarkable intrinsic molecular properties and possible strong intermolecular interactions. [1][2][3][4] So far, all reported DTT-containing organic semiconductors exhibit high charge carrier mobility and good environmental stability. Such essential features are mainly attributed to the maximization of the π-orbital overlap by restricting or even suppressing intramolecular rotations within the fused ring systems, [5][6][7] and by enhancing the conjugation length through aromatic-coupled structures, causing more rigid and coplanar conformations which facilitate the achievement of closely packed conjugated backbones.…”
Section: Introductionmentioning
confidence: 99%
“…Final product 1 was afforded through Cu 2 O oxidation. In our improved work, product 1 was prepared by three other efficient methods (Scheme ) 16. It has been confirmed that 18 and 19 can create the same thiophene dicarbanions, which are quenched with 10 to generate 1 in good yields.…”
Section: Intramolecular Cyclizations Of Bithiophene Dicarbanionsmentioning
confidence: 82%